Analysing and combining multiple credit assessments of financial institutions - Evangelos Tabakis; Anna Vinci (European Central Bank (ECB), 2002)
The last consultative papers of the Basel Committee on Banking Supervision set the path for a future where a wealth of credit assessment sources may be available. New external credit assessment institutions and internal ratings-based assessments will be added to ratings of major international rating agencies and to benchmark assessment methods used by supervisors or central banks. In its first part, this paper contributes to the development of a toolbox to analyse and compare credit assessments by examining the ratings of three leading rating agencies on a set of credit institutions. The analysis decomposes the historical default rate corresponding to a rating into two components drawing on a 'core' of published information and an 'analyst contribution'. In the second part of the paper, correlation and variance analysis of the analyst contributions lead to a combination of the available ratings, building on both the common core and the analyst part
Keywords: C21; C51; G15; G21; G28; 330